Analisis Perilaku Penggunaan Uang Non-Tunai (Studi Kasus Mahasiswa Universitas Lampung) - Putri, Reisyah Marisca; Thomas Andrian; Imam Awaluddin (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
The rapid advancement of technology in Indonesia’s financial sector, particularly through electronic money and non-cash instruments, has accelerated the shift in transaction patterns—especially since the launch of the National Non-Cash Movement (GNNT) by Bank Indonesia and the government in 2014 to promote an efficient, secure, and inclusive digital payment system. Generation Z, especially university students with a financial literacy index of 70.19% (OJK), demonstrates high adaptability to this transition. This study employs multiple linear regression to analyze the influence of income, perceived ease of use, perceived risk, and consumption expenditure on the use of non-cash payments. The findings show that income, perception, and consumption expenditure have a positive and significant effect on non- cash payment usage, shaping digital financial behavior among the youth and offering strategic insights for policymakers and financial institutions to strengthen the development of the non-cash ecosystem.